Effect of GnRH antagonist on follicular development and uterine biophysical profile in controlled ovarian stimulation - Tiwary, Bhawana; Dhaliwal, Lakhbir; Gainder, Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to assess the effect of GnRH antagonist on follicular development, premature luteinization, uterine biophysical profile and pregnancy rate in controlled ovarian stimulation with clomiphene and gonadotropins for intrauterine insemination in women with unexplained infertility. Methods: Randomised controlled trial. Minimal stimulation protocol with or without GnRH antagonist was compared. Setting: Infertility clinic, PGIMER, Chandigarh. Patients: Couples with unexplained infertility, age of female partner between 20-39 years. Intervention: GnRH antagonist 0.25 mg since follicle size 14 mm till hCG administration. Main outcome measures: Follicle characteristics, premature luteinisation, uterine biophysical profile and pregnancy rate. Results: The mean number of follicles recruited in group A was 2.32 ± 1.01 while that in group B (receiving GnRH antagonist) it was 4.10 ± 1.69. Statistically significant increase in total biophysical profile score was observed in periovulatory phase in the antagonist group. 40% women in group A had premature luteinization whereas only 4% women in group B suffered from premature luteinization. 20% women who received GnRH antagonist conceived against only 6% in group A, this difference however was not statistically significant Conclusions: GnRH antagonist has a role in increasing the number of follicles recruited. Furthermore, GnRH antagonist can improve the total uterine biophysical profile score by improving the endometrial thickness, endometrial pattern, blood flow and decreasing the impedance to the blood flow in uterine artery. The drug can potentially help in improving pregnancy rates by decreasing the rate of premature luteinisation.